2019
DOI: 10.1038/s41419-019-2021-3
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell pyroptosis plays an important role in Kawasaki disease via HMGB1/RAGE/cathespin B signaling pathway and NLRP3 inflammasome activation

Abstract: Kawasaki disease (KD) is the most common cause of pediatric cardiac disease in developed countries, and can lead to permanent coronary artery damage and long term sequelae such as coronary artery aneurysms. Given the prevalence and severity of KD, further research is warranted on its pathophysiology. It is known that endothelial cell damage and inflammation are two essential processes resulting in the coronary endothelial dysfunction in KD. However, detailed mechanisms are largely unknown. In this study, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
151
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(161 citation statements)
references
References 44 publications
9
151
1
Order By: Relevance
“…Besides, SalB significantly restored renal function in I/R mice and inhibited pyroptosis in both I/R and HK-2 cell models. Previous studies used the annexin V and propidium iodide double-positive stage and an LDH-release assay to confirm pyroptosis ( Liu W. et al, 2018 ; Jia et al, 2019 ); however, the specific cell morphology evidence of pyroptosis was lacking. Over recent years, different studies have recorded the morphology of the cells of pyroptosis by electron microscopy, despite pyroptosis occurring in different cells (HeLa cells ( Wang et al, 2017 ) and raw-asc cells), which all have the similar morphology of pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, SalB significantly restored renal function in I/R mice and inhibited pyroptosis in both I/R and HK-2 cell models. Previous studies used the annexin V and propidium iodide double-positive stage and an LDH-release assay to confirm pyroptosis ( Liu W. et al, 2018 ; Jia et al, 2019 ); however, the specific cell morphology evidence of pyroptosis was lacking. Over recent years, different studies have recorded the morphology of the cells of pyroptosis by electron microscopy, despite pyroptosis occurring in different cells (HeLa cells ( Wang et al, 2017 ) and raw-asc cells), which all have the similar morphology of pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations demonstrate that RAGE provides a transport route for extracellular HMGB1 and HMGB1-partner molecule complexes by endocytosis to the endolysosomal compartment (Deng et al 2018;Porat et al 2018;Lin et al 2019;Yang et al 2019a;Jia et al 2019;Xu et al 2014;Yang et al 2016a) (Fig. 1).…”
Section: Ragementioning
confidence: 99%
“…Previous research has shown that HMGB1 released from mouse trophoblasts contributes to inflammation during Brucella melitensis infection [ 38 ]. HMGB1 is reported to induce signalling via the RAGE receptor and the HMGB1/RAGE/cathepsin B signalling pathway, which activates NLRP3-dependent coronary endothelial cell pyroptosis and thus plays an important role in the endothelial damage that occurs in Kawasaki disease [ 39 ]. The HMGB1—RAGE proinflammatory axis promotes vascular inflammation and endothelial cell apoptosis, resulting in vascular injury during acute limb ischaemia and reperfusion [ 40 ].…”
Section: Discussionmentioning
confidence: 99%